2018
DOI: 10.1186/s13148-018-0540-x
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation and prognostic potential of 5-methylcytosine (5mC), 5-hydroxymethylcytosine (5hmC), 5-formylcytosine (5fC), and 5-carboxylcytosine (5caC) levels in prostate cancer

Abstract: BackgroundPrognostic tools for prostate cancer (PC) are inadequate and new molecular biomarkers may improve risk stratification. The epigenetic mark 5-hydroxymethylcytosine (5hmC) has recently been proposed as a novel candidate prognostic biomarker in several malignancies including PC. 5hmC is an oxidized derivative of 5-methylcytosine (5mC) and can be further oxidized to 5-formylcytosine (5fC) and 5-carboxylcytosine (5caC). The present study is the first to investigate the biomarker potential in PC for all fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 49 publications
1
36
1
Order By: Relevance
“…The TET proteins are responsible for the sequential oxidation of 5-mC into 5-hydroxymethylcytosine (5-hmC), then 5-formylcytosine (5-fC), and finally 5-carboxylcytosine (5-caC). 179 5-fC and 5-caC are shortlived intermediates of an active DNA demethylation pathway, while 5-hmC can possibly be regarded as an independent epigenetic marker. The global loss of 5-hmC has recently been proposed as a novel candidate biomarker of the presence of an aggressive tumor with both diagnostic and prognostic implications.…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%
See 1 more Smart Citation
“…The TET proteins are responsible for the sequential oxidation of 5-mC into 5-hydroxymethylcytosine (5-hmC), then 5-formylcytosine (5-fC), and finally 5-carboxylcytosine (5-caC). 179 5-fC and 5-caC are shortlived intermediates of an active DNA demethylation pathway, while 5-hmC can possibly be regarded as an independent epigenetic marker. The global loss of 5-hmC has recently been proposed as a novel candidate biomarker of the presence of an aggressive tumor with both diagnostic and prognostic implications.…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%
“…The global loss of 5-hmC has recently been proposed as a novel candidate biomarker of the presence of an aggressive tumor with both diagnostic and prognostic implications. Reduced 5-hmC levels are observed in many F I G U R E 1 Schematic diagram demonstrating the application of TCM in cancer therapy based on genetics, epigenetics, tumor microenvironment, and cancer stem cells cancers, including prostate, 179 ovarian, 180 melanoma, 181 and lung 182 cancer. In animal disease models, the growth of aggressive tumors can be thwarted by restoring 5-hmC levels via IDH2 or TET2 overexpression.…”
Section: Dna Methylation and Demethylationmentioning
confidence: 99%
“…In a similar study, TET proteins were found to suppress tumor progression and invasion partly through downregulation of critical gene methylation. 29 Storebjerg et al 30 reported TET family proteins and the epigenetic marker 5hmC to be novel candidate prognostic biomarkers. Further studies are warranted to explore the epigenetic mechanisms of TET proteins in CRPC and NEPC.…”
Section: Dna Demethylationmentioning
confidence: 99%
“…The study displayed that high 5hmC content is an independent prognosis factor of unfavorable PFS and OS in pediatric SHCC. Low 5hmC contents in most solid tumors usually means higher tumor grade and worse results [3,11,13,14,27,28]. Nevertheless, our findings displayed that high 5hmC contents were independently relevant to inferior OS in SHCC and 5hmC was possibly correlated with tumor occurrence and malignant transformation.…”
Section: Disscusionmentioning
confidence: 53%
“…5-position DNA methylation of cytosine (5mC) is an epigenetic cancer marker. Several studies have shown that the ten eleven translocation (TET) protein family initiates an active DNA demethylation pathway, leading to the transformation of 5mC into 5-hydroxymethylcytosine (5hmc) [11]. 5hmc, a novel epigenetic biomarker, is change the view of tumor epigenetics.…”
Section: Introductionmentioning
confidence: 99%